Serum CXCL5 level is associated with tumor progression in penile cancer. Issue 1 (29th January 2021) - Mo, Miao; Li, Yangle; Hu, Xiheng
Abstract: Chemokine (C-X-C motif) ligand 5 is an important regulator of tumor progression in many cancers, and could serve as potential serum cancer biomarker. Our initial analysis identified CXCL5 as a cancer-related gene highly expressed in PC. Patients with PC exhibited markedly higher preoperative serum CXCL5 levels compared with that in healthy individuals ( P <0.001). The area under the curve (AUC) was 0.880 with the sensitivity of 84.0%, and specificity of 80.4% to distinguish PC. Serum CXCL5 levels were also significantly decreased following tumor resection in patients with PC ( P =0.001). Preoperative serum CXCL5 level was significantly associated with clinicopathological characteristics including T stage ( P =0.001), nodal status ( P <0.001), and pelvic lymph node metastasis ( P =0.018). Cox regression analysis showed that serum CXCL5 level could serve as an independent prognostic factor for disease-free survival with a HR of 6.363 (95% CI: 2.185–18.531, P =0.001). CXCL5 and its receptor CXCR2 exhibited correlated expression pattern in PC tissues. Differential CXCL5 expression was observed in normal penile tissues, PC cell lines, and their culture supernatants. Furthermore, knockdown of CXCL5 or CXCR2 expression markedly suppressed malignant phenotypes (cell proliferation, clonogenesis, apoptosis escape, migration, and invasion), attenuated STAT3 and AKT signaling, and reduced MMP2/9 secretion in PC cell lines. In conclusion, our findings revealed that serum CXCL5 level might serve as a potential diagnostic and prognostic cancer biomarker for penile cancer. Autocrine CXCL5/CXCR2 signaling might activate multiple downstream oncogenic signaling pathways (STAT3, AKT, MMP2/9) to promote malignant progression of PC, which may warrant further investigation in the future.